EFFICIENCY OF LEGAL WAYS TO FIGHT AGEISM ON THE LABOR MARKET IN THE RUSSIAN FEDERATION - O. Suleymanova, Fatima (Revista Gênero e Interdisciplinaridade, 2021)
The relevance of the research is due to the fact that in Russia, same as elsewhere in the world, the ratio of older persons increases, so increases the proportion of employed older persons. This study is aimed at describing the position of older people in the labor market  for both those who have the status of a retired and those who do not have this status. The paper studies the impact of the retirement age increase on employment in the labor market, assesses the adequacy and efficiency of additional legal guarantees introduced due to the increase in the retirement age (criminal liability for the denial of employment, release from work due to annual physical, etc.). The study tries to find out how Russian labor legislation is adapted to solve problems that arise from age, and whether it is able to counteract ageism in the labor market. The research was conducted by analyzing international and Russian legislation that determines the retirement age, and the impact of the retirement age on labor market rights and employee status. The existing special legal norms regulating the labor of retired and pre-retired employees, as well as norms aimed at overcoming ageism, are considered comprehensively. In particular, the paper concludes that the current norms for regulating the labor of employed pensioners and pre-retirees are insufficient; the norms on fixed-term employment contracts with elderly pensioners are discriminatory; the criminal liability for the denial of employment of pre-retirees is inefficient, and so on. The materials of the paper may be helpful in improving the current labor and social legislation aimed at supporting older age groups in the labor market.